Preconcentration of Copper with Solid Phase Extraction and its Determination by Flame Atomic Absorption Spectrometry - Ayob Parchehbaf Jadid; Habibollah Eskandari (E-Journal of Chemistry)
A new method for the solid phase extraction (SPE) and determination of copper ions at low levels is presented. Extraction percent and the effects of some factors were evaluated. The detection limit was in the range of 2.26 µg·L-1. This procedure has been successfully applied to determination of copper in water samples.